SUNGAI LARANGAN: MEDIA PELESTARIAN EKOSISTEM FLORA FAUNA DAN KONSERVASI LINGKUNGAN BERBASIS EDUTOURISM DI DESA BILEBANTE - Persada, Ni Kadek Gita Sri; Fathurrahman, Muhammad Aryan (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2025)
The implementation of the Community Service Program (KKN) in Bilebante Village aims to implement a program to develop educational information resources regarding the Banjar River tourism based on environmental conservation for the wider community. This information media development activity focuses on providing digital media in the form of a website and non-digital media in the form of interactive maps and information bulletins related to the Banjar River. The implementation of this activity is carried out through a process of observation, interviews, documentation and preparation of activity drafts carried out for 7 weeks. The results of this activity indicate that the provision of information media about the Banjar River is very necessary, and show that UNRAM 2025 KKN students are able to design and complete the digital and non-digital information media in meeting the needs of Banjar River tourism information media for Bilebante Village tourism managers. Thus, through this program in the future, it can provide openness and easy access to information about natural tourism in Bilebante Village which can also attract more tourists to visit.